Sistem Pemantauan Kesiapan Kerja Siswa SMK Berbasis Web Menggunakan Metode Fuzzy Tsukamoto - Safrian, Rifqi; Lazulfa, Indana; Barir, Much. Zuyyinal Haqqul; Mujianto, Ahmad Heru (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2026)
This study aims to develop a web-based system for monitoring the work readiness of vocational high school students using the Fuzzy Tsukamoto method. The system is designed to assist schools in evaluating students’ levels of work readiness based on several criteria, namely academic performance, industrial work practice, and attendance. The Fuzzy Tsukamoto method is applied to transform qualitative and quantitative data into crisp values, thereby producing a more objective classification of students’ work readiness levels. This study employs a system development approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The results show that the system is able to present students’ work readiness levels in the form of categories and real-time graphical visualizations, as well as generate reports in PDF format. The system is expected to support schools in decision-making related to student guidance and job placement.